2016
DOI: 10.1111/sapm.12135
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Structured Within‐Host HIV Dynamics with Multiple Target Cells

Abstract: Human immunodeficiency virus (HIV) can infect various types of cell populations such as CD4 + T cells and macrophages. The heterogeneity of these target cells implies different birth, death, infection rates, and so on. To investigate the within-host dynamics of HIV which can infect n different types of target cells, a theoretical model with infection-age structure for each type of target cells and a general nonlinear incidence rate is proposed in this manuscript. The model, in the form of a hyperbolic system o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Thereafter, Korobeinikov et al [27,28] used a very general form f (S, I) for the incidence rate. For more other nonlinear incidence rates, we refer readers to [5,10,11,17,34,44,56].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Korobeinikov et al [27,28] used a very general form f (S, I) for the incidence rate. For more other nonlinear incidence rates, we refer readers to [5,10,11,17,34,44,56].…”
Section: Introductionmentioning
confidence: 99%
“…Models with age structure have been used in studying viral dynamics because many within-host processes, such as viral production by infected cells, may rely on the time after infection, i.e., the age of infection [31][32][33][34][35][36][37][38][39][40][41]. For example, Rong et al [42] studied age of infection models with combination therapy including reverse transcriptase inhibitor (RTI), protease inhibitor (PI), and entry/fusion inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Here x i (t) and y i (t, a) denote the amount of target uninfected CD4 + cells and infected cells, respectively. h i is the incidence rate function satisfying some conditions (see assumptions from (H1) to (H4) [5]). The authors showed that if the therapy is 100% effective, then applying the drug at late infectious stage results in a faster decay of viremia.…”
Section: )Y I (T A) Da -Cv(t)mentioning
confidence: 99%
“…The other parameters are obtained from the literature and are listed in Table 1. We choose production rates of CD4 + lymphoblasts and macrophages as λ i = 1 ml/day, i = 1, 2, respectively and the viral production rate for macrophage as p 2 (a) = 0.1 exp(-3 × 0.00028a) in [5]. The basic reproduction number is obtained, R 0 = 0.4417 < 1, which implies that the virus-free steady state E 0 is globally asymptotically stable by Theorem 2.2 and Theorem 3.1 (see Figure 1).…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation